Coordinate expression of cytokeratins 7 and 14, vimentin, and Bcl-2 in canine cutaneous epithelial tumors and cysts. (July 2015) - Pieper, Jason B.; Stern, Adam W.; LeClerc, Suzette M.; Campbell, Karen L.
Forty-seven canine cutaneous epithelial tumors and cysts were examined to determine coordinate expression of cytokeratins 7 (CK7) and 14 (CK14), vimentin, and Bcl-2 using commercially available antibodies. Within non-affected normal skin adjacent to tumors or cysts, CK7 expression was observed in luminal cells in apocrine glands; CK14 expression was observed in the stratum basale, stratum spinosum, stratum granulosum, basal layer of outer root sheath, sebaceous glands, and myoepithelial cells of apocrine glands; vimentin expression was observed in dermal papilla and scattered non-epithelial cells within the epidermis; and Bcl-2 expression was observed in scattered non-epithelial cells in the epidermis and some apocrine glands. The pattern of expression of CK7 and CK14 in cases of adenocarcinoma of the apocrine gland of the anal sac (CK7+/CK14–) and hepatoid gland tumors (CK7–/CK14+) may prove useful for diagnostic purposes. Loss of expression of CK14 and vimentin, identifying myoepithelial cells, was observed in apocrine and ceruminous adenocarcinomas. Differences in patterns of expression of Bcl-2 were observed between infundibular keratinizing acanthomas compared to trichoepitheliomas.